التدابير والإجراءات المقررة لمواجهة مخالفة قواعد البناء والتعمير - محمد الأمين, كمال (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
The phenomena of unplanned building has spread in the last few years in Algeria Strip cities and villages. This proliferation constitutes a serious violation against the regulations and legislations of organization and city building. This practice negatively affects the Algerian urban environment and leads to squandering citizens' rights to a healthy housing in the neighborhood which meets their basic hygienic, social and environmental requirements. The study handles the random building showing the nature and the forms of various breaches building regulations. Discrimination has been made between violations happening due to impossibility of gaining a building license, and breaches happening despite obtaining a license. Then the study sets out to show the effects of violations against the regulatory framework of building on the architectural environment, focusing on hygienic and environmental impact on adequate housing conditions, privacy, encroachments against streets.